La participación de la minería y sus beneficios económicos en Colombia y Perú - Espinosa Morales, Karen Julieth (Universidad Santo Tomás Tunja, 2016)
The progressive contribution of the mining sector in the economy of Colombia and Peru, major Latin American countries, has been the focus of economic development by being a producer and a source of income regarding the exportations that are favorable in the financial context. In Colombia, the variety of minerals fuels, metallic, non-metallic and precious is constantly growing, mineral fuels like coal (Guajira), metallic minerals such as copper (Chocó) and Iron (Belencito Boyacá), precious minerals Gold in (Antioquia, Bolívar, Chocó), Precious Stones, the Emeralds appreciated in the world and the important hydrocarbon oil in the Orinoco region. This amount of minerals extracted are representative for the economy of Colombia and Peru, with the passage of time the mining sector has become the largest raw materials market in the world , since increasingly mining companies join the list of operators in exploiting metals, bringing a great disinterestin the environment and consequences of great impact on our society; but if economic analyzed, such participation againstthe Gross Domestic Product, with the data supplied by the DANE (2015) which are analyzed, we obtain results which evidence representative income in the economy of each country, except that such participation is not reflected in the investment for the preservation of exploited natural resources. The case of mining in Peru has a great recognition positioning itself as the number 1 in gold mining in Latin America and being in the top 8 positions worldwide in other minerals which include Silver, Copper, and Zinc becoming a major mining operator recognized worldwide, becoming a country with the best business climate for foreign investors favoring the country’s economy. That is how, mining has brought a fairly extensive development as both Colombia and Peru want to promote a mining with social, environmental and productive responsibility, leaving economic benefits that are recognized in the statistics of each country and that can be invested in better environmental management to ecosystem conservation.